Role of ammonia in the pathogenesis of the gastritis, hypergastrinaemia, and hyperpepsinogenaemia I caused by Helicobacter pylori infection. Issue 12 (December 1992) - el Nujumi, A M; Rowe, P A; Dahill, S; Dorrian, C A; Neithercut, W D; McColl, K E
Abstract : Studies were performed in patients with and without renal failure to investigate the role of bacterial ammonia production in the pathogenesis of the mucosal abnormalities caused by Helicobacter pylori. The high rate of H pylori ammonia production in uraemic patients should accentuate any ammonia induced effects. The median (range) gastric juice ammonium concentration in the H pylori positive patients with renal failure was 19 mmol/l (II-43) compared with 5 mmol/l (1-11) in the H pylori positive patients without renal failure (p < 0.005). In the H pylori negative patients the values were 3 mmol/l (0.5-11) and 0.7 mmol/l (0.1-1.4) respectively in the patients with and without renal failure (p < 0.01). Despite the much higher ammonia production in the H pylori positive uraemic patients, the nature and severity of their gastritis was the same as that in the H pylori positive non-uraemic patients. The median (range) fasting serum gastrin concentration was raised in the uraemic patients compared with the non-uraemic patients but was similar in the uraemic patients with (95 pmol/l (52-333)) or without (114 pmol/l (47-533)) H pylori infection. The median (range) serum pepsinogen I concentration was also high in the uraemic compared with the non-uraemic patients and was significantly higher in uraemic patients with H pylori (352 ng/ml, range 280-653) than in those without H pylori infection (165 ng/ml, range 86-337) (p < 0.01). These findings indicate that the gastritis and hypergastrinaemia associated with H pylori infection are not the result of mucosal damage induced by the organism's ammonia production.